Design and development of bi-directional IoT gateway using ZigBee and Wi-Fi technologies with MQTT protocol - Gopi Krishna, P; Sreenivasa Ravi, K; Hari Kishore, K; KrishnaVeni, K; N. Siva Rao, K; D. Prasad, R (International Journal of Engineering and Technology, 2018)
With evolution of the smart things, to acquire data, gateways play a major role in interconnecting with various sensor nodes. Using different wireless protocols and standards with sensor nodes, gateway can transform information into a unique format that transmits into the cloud for further use. Which accepts the commands from external users in the remote location through a personal computer or a smartphone? The proposed gateway has its added advantages; (i) ZigBee and Wi-Fi wireless technologies connectivity is enabled, (ii) transforms the information into required protocol format, (iii) uses a light weighted MQTT protocol in transmitting and receiving environment, (iv) It provides the storage and analyzed data and (v) the sensor values can be observed and the devices can be controlled by a smartphone from remote location. Here we demonstrate the proof of concept for controlling the smart home appliances. This also represents a design and implementation of Bi-Directional IoT gateway using ZigBee and Wi-Fi technologies with MQTT protocol.